Germination Responses of Old Seeds from Lampung Local Rice to Magnetic Fields and Drought Stress - Putri, Aprilia Eka; Agustrina, Rochmah; Marjunus, Roniyus (Universitas Sultan Ageng Tirtayasa, 2024)
Germination is a critical phase in seed plants. Germination is vulnerable to drought stress. Apart from external factors, long seed storage can also affect seed viability. The magnetic field is known to positively impact the germination process because it can increase the activity of the α-amylase enzyme. Lumbung Sewu Cantik is a local upland rice variety from Lampung, Indonesia. This study aims to determine the impact of exposure to a magnetic field of 0,2 mT for 11 minutes 44 seconds (M1) in improving the germination of LSC rice seeds given accelerated aging (So) and drought by 20% PEG 6000 (D1). The parameters observed were germination rate index (GRI), mean germination time (MGT), germination index (GI), final germination percentage (FGP), and percentage of abnormal germination (PAG). This research used a Completely Randomized Design (CRD). The experimental units consisted of Sn (normal seeds as control), SoD1, SoM1, and SoM1D1. Each treatment was repeated five times. The data obtained were tested for normality, analyzed of variance, and further analyzed with DMRT at the α = 0,05 level. The results showed that the magnetic field could accelerate germination in the SoM1 treatments based on the MGT parameters. The magnetic field also reduced the percentage of abnormal seedlings in the SoM1D1 treatments compared to those without a magnetic field (SoD1 treatments).